Child Psychiatric Disorders Presenting to a Tertiary Multidisciplinary Child Development Service in Bangladesh - Islam, Farzana; Parveen, Monowara; Parvin, Rezina; Begum, Dilara; Muslima, Humaira; Khatun, Mahmuda; Mahbub, Mustafa; Khan, Naila Zaman (Bangladesh Journal of Child Health, 2012)
Background: Shishu Bikash Kendra (SBK or Child Development Center) of the Dhaka Shishu (Childrens) Hospital (DSH) has been using a multidisciplinary approach for assessment and management of children with various neurodevelopmental disorders since its establishment in 1991. In the past decade, a major proportion have presented with a range of emotional and behavioural problems. This paper aims to describe the types of child psychiatric disorders and the multidisciplinary team approach used in this centre for diagnosis and management of these children. Patients and Methods: Clinical records of 300 children who were assessed by the Child Mental Health Clinic of SBK during April 2004 to December 2006 were analyzed. These children were among the 1648 children who were referred for behavioural problems after having a General Developmental assessment (GDA). Children received services by a team comprising of child health physicians, child neurologists, child psychologists, developmental therapists and psychosocial counselors and a social worker. Psychiatric conditions were diagnosed using the multi-axial diagnostic guidelines of the Diagnostic and Statistical Manual (DSM-IV) and the International Classification of Diseases (ICD-10). The role of various clinics of the SBK to address specific aspects of a childs mental health condition is described. Results: Of the 300 children seen 55% were of primary school age (ie, between 5-10 years), boys comprising 71%. The majority (94%) could be categorized into a psychiatric condition. Sixty three percent had a developmental problem. In addition, with 44% children having some intellectual deficit. Sixty one percent had an associated neurological or general medical condition. It was important to note also that 54% had some form of psychosocial adversity which needed immediate help. Commonest psychiatric diagnosis was Hyperkinetic Disorders (33%) followed by Autism Spectrum Disorders (ASD) and other Pervasive Developmental Disorders (PDD) (27%). Conclusion: Psychiatric morbidity is a common presentation among children who come to the child development and neurodisability service. If Child Mental Health professionals work with a multidisciplinary team within a child development service such as SBK, it may best utilize the multiaxial diagnosis system. DOI: http://dx.doi.org/10.3329/bjch.v35i3.10385 Bangladesh J Child Health 2011; Vol 35 (3): 84-89